2003
DOI: 10.1242/dev.00666
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of Brn1 in distal tubule formation and function in mouse kidney

Abstract: This study identifies a role for the gene for the POU transcription factor Brn1 in distal tubule formation and function in the mammalian kidney. Normal development of Henle's loop (HL), the distal convoluted tubule and the macula densa was severely retarded in Brn1-deficient mice. In particular, elongation and differentiation of the developing HL was affected. In the adult kidney, Brn1 was detected only in the thick ascending limb (TAL) of HL. In addition, the expression of a number of TAL-specific genes was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 23 publications
7
138
0
Order By: Relevance
“…Studies of several signaling pathways, as well as transcription factors, have revealed genes involved in the patterning the nephron including Fgf8 (Grieshammer et al, 2005), Pou3f3 (Nakai et al, 2003),Sprouty (Basson et al, 2005;Basson et al, 2006), Notch/presenillins (Cheng et al, 2007;Cheng et al, 2003;McCright et al, 2002), and Lhx1 (Kobayashi et al, 2005). In particular, genetic studies have shown several members of the Wnt family of lipidmodified secreted glycoproteins have important roles in the initiation and maintenance of nephron formation and branching morphogenesis Kispert et al, 1998;Majumdar et al, 2003;Stark et al, 1994).…”
Section: Screen For Genes In Nephron Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of several signaling pathways, as well as transcription factors, have revealed genes involved in the patterning the nephron including Fgf8 (Grieshammer et al, 2005), Pou3f3 (Nakai et al, 2003),Sprouty (Basson et al, 2005;Basson et al, 2006), Notch/presenillins (Cheng et al, 2007;Cheng et al, 2003;McCright et al, 2002), and Lhx1 (Kobayashi et al, 2005). In particular, genetic studies have shown several members of the Wnt family of lipidmodified secreted glycoproteins have important roles in the initiation and maintenance of nephron formation and branching morphogenesis Kispert et al, 1998;Majumdar et al, 2003;Stark et al, 1994).…”
Section: Screen For Genes In Nephron Formationmentioning
confidence: 99%
“…Some genes failed to meet the statistical cutoff though they are expressed in E14.5 kidney. These included Fgf8 (Grieshammer et al, 2005), ret (Pachnis et al, 1993;Schuchardt et al, 1994), Pou3f3 (Nakai et al, 2003), Wnt7b (Kispert et al, 1996;Patterson et al, 2001), Ihh (Valentini et al, 1997), and Shh (Yu et al, 2002). Overall, the wildtype profiles had 6824 Present calls (54.9%) and the Wnt4 mutant profiles had 6628 Present calls (53.4%).…”
Section: Transcriptional Profiling Of Wnt4 Mutant Kidneysmentioning
confidence: 99%
“…Far less is known how the more distal nephron segments are specified. Mouse embryos that lack Brn1 (Pou3f3), a POU domain transcription factor, initiate nephrogenesis but form truncated nephrons that lack the loop of Henle and distal tubules (Nakai et al 2003). Whether Brn1 is sufficient to specify these nephron segments is not known.…”
mentioning
confidence: 99%
“…DLL1 contributes via NOTCH2 in the specification of proximal tubule fate (12,35). Under the control of transcription factors BRN1 and Iroquois-class homeodomain proteins IRX 1-3, distal segments further extend and differentiate toward the distal tubule and Henle's loop (46,49,76) (Fig. 1).…”
Section: Transcriptional Network In Nephron Patterningmentioning
confidence: 99%
“…1). Brn1Ϫ/Ϫ mutant mice show disrupted development of Henle's loop and formation of distal convoluted tubules (46). In X. laevis, a subset of Irx transcription factors (Irx1, Irx2, and Irx3) are specifically expressed in a medial zone of the developing pronephric anlagen, which will give rise to the intermediate tubule.…”
Section: Transcriptional Network In Nephron Patterningmentioning
confidence: 99%